Exploring the impact of bilingual education on student outcomes: A qualitative student-centric approach - Gnana Sanga Mithra S; Ananth Padmanabhan (Science Talks, 2025)
This qualitative study explores the impact of bilingual education in Tamil and English on student comprehension and academic performance from the perspective of students in Tamil Nadu. It investigates students' attitudes toward bilingual learning, language preferences, and the perceived effectiveness of teaching strategies within a dual-language framework. Using case studies, in-depth interviews, and focus groups, the study captures detailed insights into students' bilingual learning experiences. Grounded in the Tamil-English bilingual context, the literature review draws on key theories of bilingualism and language acquisition, including Cummins' Threshold Hypothesis, the Bilingual Interactive Activation Model, and Vygotsky's Sociocultural Theory. The study also incorporates the concept of translanguaging—the fluid use of multiple languages to maximize learning—and cognitive flexibility, defined as the mental ability to switch between thinking about different concepts or languages. Data is analyzed through thematic analysis, identifying recurring patterns related to student engagement, comprehension, and learning outcomes. Findings indicate the need to refine bilingual education practices in Tamil Nadu to better align with students' language preferences, support cognitive development, encourage cultural integration, and promote effective, student-centered instruction. Such refinements could help bridge the gap between theoretical frameworks and the practical realities of bilingual learning in regional educational settings.